Bilateral variation in origin of facial artery in a cadaver - Kumal, Jay Prakash Prasad; Timsina, Ram Prasad; Yadav, Sanjay Kumar; Gogoi, Pramananda (Journal of Kathmandu Medical College, 2015)
Anatomical knowledge of the origin, course, and branching pattern of the facial artery is important for surgeons and radiologist. However abnormal pattern of facial artery may change the result of the treatment, if it is not predicted in advance. Here we report bilateral variation in origin of facial artery originated as a linguo-facial trunk from external carotid artery.Journal of Kathmandu Medical CollegeVol. 3, No. 4, Oct.-Dec., 2014Page: 171-173